2022
DOI: 10.1186/s13054-022-04153-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma SARS-CoV-2 nucleocapsid antigen levels are associated with progression to severe disease in hospitalized COVID-19

Abstract: Background Studies quantifying SARS-CoV-2 have focused on upper respiratory tract or plasma viral RNA with inconsistent association with clinical outcomes. The association between plasma viral antigen levels and clinical outcomes has not been previously studied. Our aim was to investigate the relationship between plasma SARS-CoV-2 nucleocapsid antigen (N-antigen) concentration and both markers of host response and clinical outcomes. Methods SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…Our study also demonstrates a strong association of SARS-CoV-2 nucleocapsid viral antigen with development of severe disease in COVID-19, consistent with several prior studies of hospitalized patients ( 14 , 19 , 20 , 40 ). Recent data from a large multicenter clinical trial consortium demonstrated that in patients hospitalized with COVID-19, higher SARS-CoV-2 nucleocapsid viral antigen measured within the first 72 hours was associated with worse clinical outcomes at 7 days ( 19 ). At a threshold of 1,000 pg/ml, the viral antigen was 77% sensitive and 59% specific for a worse outcome on the WHO ordinal scale at 7 days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also demonstrates a strong association of SARS-CoV-2 nucleocapsid viral antigen with development of severe disease in COVID-19, consistent with several prior studies of hospitalized patients ( 14 , 19 , 20 , 40 ). Recent data from a large multicenter clinical trial consortium demonstrated that in patients hospitalized with COVID-19, higher SARS-CoV-2 nucleocapsid viral antigen measured within the first 72 hours was associated with worse clinical outcomes at 7 days ( 19 ). At a threshold of 1,000 pg/ml, the viral antigen was 77% sensitive and 59% specific for a worse outcome on the WHO ordinal scale at 7 days.…”
Section: Discussionsupporting
confidence: 91%
“…We therefore hypothesized that RAGE would be a useful early biomarker of disease severity in patients with COVID-19. Additionally, viral load measured by plasma SARS-CoV-2 ribonucleic acid (RNA) or by plasma SARS-CoV-2 nucleocapsid viral antigen is known to be associated with disease severity ( 19 22 ). However, to what extent plasma SARS-CoV-2 nucleocapsid viral antigen correlates with RAGE and with ultimate disease severity early in patients’ disease course is not well described.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating NCP antigen is detected at higher concentrations in severely ill COVID19 patients [7,[9][10][11]. Our study identified a moderate but significant correlation between NCP antigenemia and CRP / IL-6 in ICU patients.…”
Section: Discussionmentioning
confidence: 50%
“…Our study identified a moderate but significant correlation between NCP antigenemia and CRP / IL-6 in ICU patients. Earlier investigations had observed an association of higher NCP antigenemia with CRP [6], IL-10, IP-10 and RAGE [10]. As a prognostic marker, NCP concentrations of >1000 pg/mL upon hospitalization were associated with later ICU admission and delayed hospital discharge [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…The specificity and relatively high sensitivity of this direct analysis has been shown in fluorescence immunochromatographic (FIC) assays [ 15 ] and ELISA tests [ 16 , 17 ]. Moreover, strong positive correlation was observed between elevated plasma N-antigens and odds of pulmonary damage severity, resulting in worsened clinical outcomes [ 17 , 18 ]; therefore, N-level measurement upon hospital admission may improve risk stratification through identification of patients with implicit odd of severe diseases [ 18 ]. An N-antigen-based assay may be performed in a simple self-test format, although its sensitivity and diagnostic accuracy would be lower compared to those of an RT-PCR assay [ 19 ].…”
Section: Introductionmentioning
confidence: 99%